The heart of Russia : Trinity-Sergius, monasticism, and society after 1825 - Kenworthy, Scott M. (Woodrow Wilson Center Press : Oxford University Press, 2010)
Studies in particular monastic revivals in the 19th and 20th centuries, as epitomized by Trinity-Sergius.